Elderly patient with ureteric colic: suspect leaking aneurysm - Sinha, Yashashwi (BMJ Publishing Group, 2013)
Described below is a case of a 72-year-old man with an abdominal aortic aneurysm (AAA) presenting with symptoms of renal colic. This case illustrates the hazards of making a diagnosis of renal colic in an elderly patient without considering the diagnosis of a leaking AAA. The diagnosis of an AAA can be challenging and renal colic is the single most common misdiagnosis. The patient's initial presentation can be misleading as symptoms fit the features of renal colic or a leaking AAA. Despite normal haemoglobin, microscopic haematuria and a dilated ureter on intravenous urogram (IVU); a leaking AAA should still have been considered. An ultrasound or CT (rather than an IVU) scan would have confirmed the appropriate diagnosis. A high degree of suspicion, early identification and surgical intervention can help reduce the high incidence of mortality in such cases.